2023
DOI: 10.1002/eng2.12644
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermal properties of Al/MoO3 thermite by electrostatic spraying

Abstract: To improve the thermal properties of thermite safely and stably, electrostatic spraying was used to prepare the Al/MoO 3 thermite. The Al/MoO 3 thermites were detected and characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD), and thermal decomposition experiments were carried out by differential scanning calorimetry (DSC). The heat release of the Al/MoO 3 thermite prepared by the electrostatic spray (1044 J g −1 ) is significantly higher than that of the thermite prepared by the ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Other studies have demonstrated that aluminum-based thermites exhibit elevated heat release characteristics, wherein the heat release of Al/MoO 3 is significantly higher in comparison to other thermite compositions [58,65]. The critical reaction temperature of super thermites undergoes a diminution of 200-400 • C upon the addition of aluminum nanoparticles, implying an enhanced reactivity [58].…”
Section: Combustion Properties and Characteristics Of Aluminum-based ...mentioning
confidence: 99%
“…Other studies have demonstrated that aluminum-based thermites exhibit elevated heat release characteristics, wherein the heat release of Al/MoO 3 is significantly higher in comparison to other thermite compositions [58,65]. The critical reaction temperature of super thermites undergoes a diminution of 200-400 • C upon the addition of aluminum nanoparticles, implying an enhanced reactivity [58].…”
Section: Combustion Properties and Characteristics Of Aluminum-based ...mentioning
confidence: 99%